First description of in situ chlorophyll fluorescence signal within East Antarctic coastal polynyas during fall and winter - Bourreau, Lucie; Pauthenet, Etienne; Le Ster, Loïc; Picard, Baptiste; Portela, Esther; Sallée, Jean-Baptiste; McMahon, Clive R.; Harcourt, Robert; Hindell, Mark; Guinet, Christophe; Bestley, Sophie; Charrassin, Jean-Benoît; et al. (Frontiers in Marine Science, 2023)
Antarctic coastal polynyas are persistent and recurrent regions of open water located between the coast and the drifting pack-ice. In spring, they are the first polar areas to be exposed to light, leading to the development of phytoplankton blooms, making polynyas potential ecological hotspots in sea-ice regions. Knowledge on polynya oceanography and ecology during winter is limited due to their inaccessibility. This study describes i) the first in situ chlorophyll fluorescence signal (a proxy for chlorophyll-a concentration and thus presence of phytoplankton) in polynyas between the end of summer and winter, ii) assesses whether the signal persists through time and iii) identifies its main oceanographic drivers. The dataset comprises 698 profiles of fluorescence, temperature and salinity recorded by southern elephant seals in 2011, 2019-2021 in the Cape-Darnley (CDP;67˚S-69˚E) and Shackleton (SP;66˚S-95˚E) polynyas between February and September. A significant fluorescence signal was observed until April in both polynyas. An additional signal occurring at 130m depth in August within CDP may result from in situ growth of phytoplankton due to potential adaptation to low irradiance or remnant chlorophyll-a that was advected into the polynya. The decrease and deepening of the fluorescence signal from February to August was accompanied by the deepening of the mixed layer depth and a cooling and salinification of the water column in both polynyas. Using Principal Component Analysis as an exploratory tool, we highlighted previously unsuspected drivers of the fluorescence signal within polynyas. CDP shows clear differences in biological and environmental conditions depending on topographic features with higher fluorescence in warmer and saltier waters on the shelf compared with the continental slope. In SP, near the ice-shelf, a significant fluorescence signal in April below the mixed layer (around 130m depth), was associated with fresher and warmer waters. We hypothesize that this signal could result from potential ice-shelf melting from warm water intrusions onto the shelf leading to iron supply necessary to fuel phytoplankton growth. This study supports that Antarctic coastal polynyas may have a key role for polar ecosystems as biologically active areas throughout the season within the sea-ice region despite inter and intra-polynya differences in environmental conditions.